The Role of Mindfulness in the Intimate Relationships and Psychological Wellbeing in Emerging Adulthood - María de Lourdes Rosales-Villacrés; Cristián Oyanadel; Diana Changotasig-Loja; Ignacio Betancourt-Peters; Wenceslao Peñate-Castro (Social Sciences, 2021)
Little is known about the impact of mindfulness on psychological wellbeing, anxiety, and avoidance in couple relationships. In emerging adulthood, intimate relationships are associated with life satisfaction and changes that can cause psychological maladjustment. This study seeks to determine if dispositional mindfulness acts as a protective variable between psychological wellbeing, anxiety, and avoidance and identify the factors that are protectors. A sample was obtained of 391 young university students between 18 and 25 years old. The Five-Facet Mindfulness Questionnaire, the Ryff Scales of Psychological Wellbeing, and the Experiences in Close Relationships Scale were used. The results show that the highest levels of dispositional mindfulness are associated with greater psychological wellbeing. Dispositional mindfulness cannot act as a protective variable against anxiety and avoidance, and values were non-significant in intimate relationships. It is necessary to continue investigating the most protective facets of mindfulness for both anxiety and avoidance.